2019
DOI: 10.23822/eurannaci.1764-1489.126
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare costs associated with allergic rhinitis, asthma allergy immunotherapy

Abstract: Allergic rhinitis (AR) and asthma are chronic diseases in which the airways become inflamed in response to allergens. Allergy immunotherapy (AIT) is recommended for those unable to manage symptoms using pharmacotherapy. This study estimated healthcare costs and utilisation for patients with AR and asthma. Mean annual outpatient visits, pharmaceutical costs and inpatient hospitalisations were calculated for 2010 and 2014, with pharmaceutical and inpatient costs stratified by AIT use. AR and asthma patients had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Previous studies have either reported HRU and costs based on estimates only 7 or reported data for short time periods (1-2 years). 8 This analysis of real-world data found that the initial added HRU and costs with AIT during the recommended treatment period are offset in the long term during the 9-year follow-up period.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have either reported HRU and costs based on estimates only 7 or reported data for short time periods (1-2 years). 8 This analysis of real-world data found that the initial added HRU and costs with AIT during the recommended treatment period are offset in the long term during the 9-year follow-up period.…”
Section: Resultsmentioning
confidence: 92%
“…Published evidence shows that there are considerable cost savings to be made with the use of appropriate allergy therapy, 7 and that AIT use is associated with appreciably lower costs than with no AIT use. 8 However, such studies have not evaluated whether the long-term benefits of AIT (ie, reductions in hospitalizations and symptomatic pharmacotherapy) are sufficient to offset the short-term costs of the treatment and its administration.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, patients often require multiple medications for relief of symptoms and often a lifelong course of treatment. [6][7][8] The principle of allergen immunotherapy (AIT), also known as desensitization, considers gradual exposure of patient to increasing amounts of triggering allergen over a period to allow the immune system to build natural tolerance, relieve symptoms, reduce the use of allopathic medicines, and improve patient's quality of life. 8 Since physicians play a fundamental role in patient's adherence to the treatment, 9 it is important to ensure that they have an adequate level of AIT knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…While mortality, severity, and prevalence vary widely geographically, the prevalence of this disease in Germany is estimated to be approximately 5% in adults and 10% in children [ 29 , 30 , 31 , 32 , 33 ]. Asthma remains one of the costliest disorders and imposes a significant burden on society and patients, resulting in 11.0 million physician visits and 1.7 million emergency room visits, and is the leading cause of missed school days [ 29 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%